Modelo para la evaluación de habilidades profesionales en un sistema de laboratorios a distancia - Mar Cornelio, Omar; Gulín González, Jorge (Revista Científica, 2018)
The evaluation of student behavior in the development of their professional activities represents an important element to measure their academic performance. At the Central University Martha Abreu de las Villas, professional practices are implemented at distances through a system of remote laboratories. However, there are no procedures to mediate professional skills. The present investigation describes a solution to the problematic raised from the development of a model for the evaluation of professional abilities for the system of remote laboratories. The proposed model uses a multiexpert multicriteria approach with the use of a diffuse cognitive map to represent causal knowledge. Two experiments are applied to test the impact of the proposal using the Wilconxon signed nonparametric range test. It was obtained as a result of the first experiment that there is a significant statistical difference of the access control inferred by the model with respect to the total of people who developed the laboratory practices; In the second experiment it was found that there is no significant statistical difference in access control inferred by the model with respect to the successful development of laboratory practices. The results corroborate that its application guarantees the diagnosis of professional skills for access control of laboratory practices in the system of remote laboratories.